Multiprofessional care for people with mental disorder in primary health care: Experience report (Research, Society and Development, 2024)
Multidisciplinary care stands out as a strategy that serves to strengthen mental health actions in Primary Health Care (PHC). The objective was to describe the practical experience of a health team related to people with mental disorders, monitored by PHC, through a case study. It was an experience report, divided into: choice and description of the case; application of Mental Health Risk Stratification; presentation of the actions of the multidisciplinary team. The doctor worked on the medication treatment; the psychologist, in psychotherapy; the social worker, in conflict mediation and in the search for social benefits; the dentist, in dental treatment; the nurse, in the organization of services and biopsychosocial-cultural guidelines. It is suggested that more studies be developed that address this topic, in order to provide results of experiences, which will serve for the emergence of other mental health actions in PHC.